ANALYSIS OF THE RHETORIC OF SAID AQIL SIROJ'S RELIGIOUS DAKWAH AS A MEANS OF ISLAMIC DAKWAH EDUCATION - Ahdori, Abdul Rahman; Subhan, Arief; Zamhari, Arif (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Purpose: This study analyzes the rhetoric of Said Aqil Siroj’s religious dakwah as an instrument of Islamic dakwah education. The research focuses on how rhetorical strategies are employed to convey Islamic values, promote moderation, and foster educational messages within diverse social and cultural contexts. Method: Using a qualitative approach, this study applies rhetorical analysis to selected sermons, speeches, and public statements delivered by Said Aqil Siroj. The analysis examines key rhetorical elements, including ethos, pathos, and logos, as well as language style, argumentation patterns, and symbolic expressions. Result: The findings indicate that Said Aqil Siroj’s dakwah rhetoric emphasizes inclusivity, tolerance, and contextual interpretation of Islamic teachings, making his messages accessible and educational for a broad audience. Conclusion: His rhetorical approach integrates religious authority with social awareness, enabling dakwah to function not only as spiritual guidance but also as a medium for Islamic education that encourages critical thinking, social harmony, and religious moderation. This study concludes that effective religious rhetoric plays a significant role in strengthening Islamic dakwah education and shaping constructive religious understanding in contemporary society.